Oxidation mechanism of MAX phases (Ti3AlC2 powders) with and without Sn doping. (March 2021) - Guo, Chunyu; Wang, Enhui; Wang, Shuize; Hou, Xinmei; He, Zhijun; Liang, Tongxiang; Chou, Kuo-Chih
Highlights: DFT calculation showed that Sn doping weakened the Ti-Al bonds in Ti3 AlC2 . The oxidation of Ti3 AlC2 and Ti3 Al0.8 Sn0.2 C2 powders was controlled by diffusion. There were three stages of both powders depending on the temperature. Kinetic analysis verified the accelerating effect of Sn doping on Ti3 AlC2 powders. Abstract: The oxidation behaviors of Ti3 AlC2 and Ti3 Al0.8 Sn0.2 C2 powders in air over the temperature range from 450 to 900 ℃ have been comprehensively compared. First-principles calculations suggest that Sn doping can decrease the oxidation resistance of Ti3 AlC2 powders due to its weakening effect on the Ti-Al bonds. There are three stages of both powders depending on the oxidation temperature, in which the oxidation behaviors vary enormously with specific morphologies. Based on this, real physical picture (RPP) model is adopted to discuss the oxidation kinetics, which further verifies the accelerating effect of Sn doping on the oxidation process of Ti3 AlC2 powders.